Strategies for Achieving Sustainable Competitive Advantage to Enhance Company Performance - Hari Tohar Muljono; Abdul Malik Hasyim (Jurnal Ilmu Manajemen Profitability, 2023)
This study outlines a sustainable competitive advantage strategy aimed at enhancing company performance. Contingency theory is employed to elucidate strategies linked to the external business environment, thereby determining company performance. Additionally, the Resource-Based View (RBV) theory expounds upon the resources possessed by companies, with the intention of bolstering company performance within the context of a highly competitive global business landscape. The method employed in this study involves the utilization of library research methodology (library research). The findings of this study underscore that the strategy employed encompasses a business approach enabling companies to attain sustainable competitive advantage. This encompasses various facets such as the strategy type, strategic mission, and strategic positioning. Fundamentally, a sustainable competitive advantage strategy in business necessitates the identification of opportunities and an ongoing commitment to innovation to differentiate the company from its peers and mitigate imitation risks. Continuous innovation serves as a catalyst towards ultimately achieving a sustainable competitive advantage. Furthermore, the company undertakes a diversification strategy to heighten corporate value. Through diversification, the anticipation is for the company to yield increased profitability.